Multi-objective optimized management of electrical energy storage systems in an islanded network with renewable energy sources under different design scenarios - Ippolito, M.G.; Di Silvestre, M.L.; Riva Sanseverino, E.; Zizzo, G.; Graditi, G. (Energy (Oxford), 2014)
The subject addressed in this paper is the definition of some strategies for the design and the optimaized management of EES (Electrical Energy Storage) systems, for an existing islanded distribution network supplying the Island of Pantelleria (Italy) in the Mediterranean Sea.